Global commodity markets and development economics - Pfaffenzeller, Stephan (New York : Routledge, 2018)
"The early 21st century has seen a prolonged price boom in non-fuel commodities, coupled with a volatile performance in fuel prices. This new collection presents the latest research on commodity prices and economic development in the context of this changing globalized economy.Global Commodity Markets and Development Economics brings together analyses from a number of perspectives in order to explore commodity price developments. Chapters explore long term commodity trends, the evolution of relative price developments, the relationship of the domestic commodity sector with global supply chains, agri-food prices, and the role of oil markets in the global economy. Through considering a diverse range of countries including China, Russia and the United States, the authors examine key fuel and non-fuel commodity markets and offer a window into important trends and developments.This book will be relevant to those with an interest in development economics, international economics and energy markets."--Provided by publisher.
Introduction / Stephan Pfaffenzeller -- The resource curse, commodity prices and economic growth / David I. Harvey, Neil Kellard, Jakob B. Madsen and Mark E. Wohar -- Which terms of trade : recent developments in relative commodity prices / Stephan Pfaffenzeller -- A diversification path for resource intensive economies / Masuma Farooki -- Rice market integration in India / Madhusudan Ghosh and Atanu Ghoshray -- Do export restrictions reduce domestic price volatility? : evidence from the wheat export controls in Kazakhstan, Russia and Ukraine / Linde Gotz and Ivan Djuric -- The impact of peak oil on trade globalisation : an example of steel exports from Europe and North America to the United States / Jan Moldenhauer -- The role of trade in energy security for developing nation's and a globalised economy / Xu Tang, Simon Snowden and Mikael Hok.
Keywords: Commodity exchanges; Commercial products; Prices; Economic development; Business logistics